The Influence of Financial Literacy, Financial Technology on Financial Inclusion Mediated by Cashless Policy - Adhela Ghina Rachmatika; Muhammad Saifi; Saparila Worokinasih (Journal of Indonesian Applied Economics, 2023)
Purpose The study aims to review access to payment system services, awareness and knowledge in the Sempaja Shopping Tourism Area so that it can evaluate appropriate policies to transform the economy cash-based to a non-cash economy Design/methodology/approach The research method used in this research is quantitative research with the nature of research is explanatory research. Data collection techniques are questionnaires and interviews. Findings Financial literacy, financial technology, cashless policy, and financial have strong and positive effects to the objectives of the study. Research limitations/implications         This research has limitations in the sampling were not all of these MSMEs have switched to digital so for further research it would be better to use a sample of MSMEs that have switched to digital use. Originality/value This study seeks to evaluate the implementation of bankaltimtara policies with a view to assessing the prospects and challenges that are factors in encouraging financial inclusion.